Deliberative intentionality: Examples of striking letters in the Qur’anic discourse (Journal of the College of Basic Education, 2024)
Praise be to God, Lord of the Worlds, and prayers and peace be upon the Master of the Messengers, our master Muhammad, and upon the God of the pure, his righteous companions, and those who followed their path until the Day of Judgment and beyond.The idea of ​​this research came when we were reading in the Book of God, and we passed some verses containing the letters of the strike, so we find the textual and performance transformations of the Qur’anic discourse when we reach these letters and beyond, so the title of the research came: Intentional deliberative models of the letters of the strike in the Qur’anic discourse. Because intentionality is a pragmatic presumption that highlights and sheds light on the discourse, and discourse is a fabric that is built on a number of cognitive, cognitive, and other levels, and the letters of the alphabet shed light on the intentionality of the transmission to the recipient.Therefore, this research was divided into two sections and a conclusion. In the first topic, I dealt with introductions to the methodological fields adopted in this research. I dealt with it first: the concept of intentionality as a language and idiomatic for the Arabs and the West, and secondly, it was about the letters of the strike, in which it dealt with the number of the letters of the strike, their meanings, the terms of their actions and the difference Among these letters, the third came about the concept of the Qur’anic discourse, while the second topic came by choosing models from the Qur’anic discourse that contain the strike letters according to the different divisions of each tool.